Ritual Communication in Rebo Bontong Culture in Pernggabaya Village, East Lombok - Ellys Lestari Pambayun; Selly Rohmayuni; M. Imam Firdaus; Abdul Quddus; Siti Salwa (International Journal of Sustainable Applied Sciences, 2023)
The Rebo Botong ritual is an ancestral heritage of the Sasak tribe in East Lombok, NTB, whose aim is to ward off danger and maintain the safety of its citizens. Although, applying Islamic teachings by using prayers and reading verses of the holy Qur'an as well as praying to the Prophet SAW, this does not prevent oneself from the pros and cons of a society that is modern and has a different understanding of the Islamic religion. The theoretical framework of this study uses a ritual communication and cultural da'wah approach, and the method chosen is a case study with in-depth interviews and field observations with five people, with the criteria: one person (traditional leader), two people (educator and activist), and 2 people ordinary residents of the Sasak Tribe (Pringgabaya Village) East Lombok. The results of this research found that the Rebo Botong ritual was carried out to preserve ancestral culture with an Islamic framework and local traditions, and is now developing into tourism and attracting sponsors who can promote this ritual. Although, some residents no longer follow the Rebo Botong ritual because their educational background and religious understanding are different from those of the Sasak tribe who still adhere to this custom.